"Finest Gossamore": Cavalier materials and fragile metaphors. Issue 4 (2nd October 2017) - Burlinson, Christopher
ABSTRACT: This article uses the substance of gossamer to rethink some connections between Cavalier poetics, costume and aesthetics. It begins with a discussion of a group of poems by Robert Herrick and investigates a particular kind of metaphorical structure in which substances and individuals are not quite transformed, and in which poems unravel or end abruptly rather than following or completing their metaphors. It goes on to track spiders' webs and in particular gossamer (a substance caught between the material world and the imagination, the point where web unravels into thread, where artifice vanishes) through Herrick's poetry and elsewhere, particularly Robert Hooke's Micrographia . It then goes on to discuss the recurrence of threadbareness in satirical accounts of Cavalier costume from the 1640s and later: these writings often pitch the Cavalier as individuals not quite transformed into the identity of their costumes.